2017
DOI: 10.1111/dth.12468
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture plus moxibustion for herpes zoster: A systematic review and meta-analysis of randomized controlled trials

Abstract: Herpes zoster is an acute inflammatory condition which can have a significant impact on quality of life. Antiviral therapies are effective, but do not meet patients' expectations of symptomatic relief. Acupuncture and moxibustion have been used for herpes zoster; this systematic review evaluated their efficacy and safety. Nine English and Chinese databases were searched from their inceptions to March 2016. Randomized controlled trials evaluating the combination of acupuncture plus moxibustion in adult herpes z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 30 publications
(72 reference statements)
2
33
0
Order By: Relevance
“…A cross-sectional study investigated that the pain was the top acupuncture indications and was nearly half of the clinical problem acupuncturists encountered in the US clinics [6]. Acupuncture was reported for the treatment of HZ [7][8][9][10], which showed that it relieves pain of HZ, shortens the healing of the rash, and reduces the occurrence of postherpetic neuralgia (PHN). But no studies have evaluated the reporting quality of these papers.…”
Section: Introductionmentioning
confidence: 99%
“…A cross-sectional study investigated that the pain was the top acupuncture indications and was nearly half of the clinical problem acupuncturists encountered in the US clinics [6]. Acupuncture was reported for the treatment of HZ [7][8][9][10], which showed that it relieves pain of HZ, shortens the healing of the rash, and reduces the occurrence of postherpetic neuralgia (PHN). But no studies have evaluated the reporting quality of these papers.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the cumulative medical cost is high for such treatments on this disease, and patients are not fully satisfied even with the curative effect. With all these downsides of conventional drug therapies, it is said to believe complementary and alternative medicine such as acupuncture may give better results with less side effects and reduce medical costs to treat HZ infection [3,4]..…”
Section: Introductionmentioning
confidence: 99%
“…With all these downsides of conventional drug therapies, it is said to believe complementary and alternative medicine such as acupuncture may give better results with less side effects and reduce medical costs to treat HZ infection. [3][4] .…”
Section: Introductionmentioning
confidence: 99%